Pengetahuan Gizi dan Pola Asuh Ibu Anak Balita Gizi Kurang di Kelurahan Pasteur Kecamatan Sukajadi Bandung - Subekti, Sri; Yulia, Cica (INVOTEC, 2012)
Nutrition knowledge is principal issues related to various nutritional problems that occur in Indonesia. Maternal role in children’s growth and development is very dominant, that is in caring for and educating them. Parenting patterns applied by the mother can affect the growth of the children, especially the nutritional status. Goals to be achieved in this study are: 1) to inquire nutrition and health knowledge of mothers with malnutrition children; 2) to examine food and health parenting pattern applied by mothers with malnutrition children and 3 ) to analyze the relationship between nutrition and health knowledge and parenting pattern implemented by the mother. The method used in this study is the Cross-Sectional. The results show that more than half of mothers’ nutrition and health knowledge is in medium category. More than half of mothers’ food parenting pattern is in fairly good category. Whereas, mothers’ health parenting pattern is in good category. Toddlers’ nutritional status, as measured using anthropometry, is generally in normal category. Spearman correlation test results state that there is a positive and significant relationship, and thus it can be concluded that the higher the mother's nutrition knowledge score, the better the food parenting pattern.